LGBTQ+ domestic and family violence victim-survivors’ experiences of remote court hearings during the COVID-19 pandemic: The gendered dimensions of safety, independence and visibility - Reeves, Ellen (Criminology & criminal justice, 2025)
There was a significant uptake of remote court hearings during the COVID-19 pandemic for family violence intervention order applications in Victoria, Australia. Remote court hearings can alleviate the burden associated with victim-survivors appearing in court and confronting their alleged perpetrator, and facilitate the efficiency of justice processes. Most research on remote justice models that facilitate victim-survivors’ protection or participation has accounted for practitioner observations, leaving a gap in understanding of how victim-survivors experience remote hearings. Drawing on interviews with 11 lesbian, gay, bisexual, transgender and queer (LGBTQ+) domestic and family violence victim-survivors who participated in remote family violence intervention order hearings in Victoria during the pandemic, this article reveals that while remote hearings can promote feelings of safety, control and procedural justice, the process can also work to invisiblise some victim-survivors. Ultimately, we find that these tensions reflect the gendered dimensions and experiences that monopolise the intervention order process more generally.